Application of volumetric method to the assessment of damage induced by action of foreign object on gas pipes - Adib, R.; Schmitt, C.; Pluvinage, G. (Проблемы прочности, 2006)
Gas pipes are submitted to three major types of damage: damages induced by impact of foreign objects, pits and craters produced by corrosion, weld defects produced during manufacturing. Damages induced by impact of foreign objects are considered as the most important problem for the gas pipes reliability and lead to dents, gouges or notches at the pipe failure. Geometrical effect of gauges or notches on brittle or elastoplastic failure of pipes submitted to internal pressure can be treated by the volumetric method. The volumetric method has been applied to a gas pipe submitted to internal pressure and exhibiting a longitudinal external and surface notch. We introduced a special procedure (SINTAP), which allows one to compute the safety factor value.